The Effect of Work Climate and Leadership Style on Job Satisfaction of Production Operators at PT. X - Artia, Risa; Akbar, Rifqi Farisan (International Journal of Marketing & Human Resource Research, 2025)
This study investigates the influence of work climate and leadership style on job satisfaction among production operators at PT X. Employing a quantitative approach with an explanatory research design, the study included all production operators as the population, selected through purposive sampling. Data were collected using three validated and reliable instruments: the Job Satisfaction Scale, the Work Climate Scale, and the Leadership Style Scale. Multiple linear regression analysis was employed to examine the relationships between variables. The findings reveal that both work climate and leadership style simultaneously have a significant effect on job satisfaction (R² = 0.805; p < 0.05). Moreover, the partial analysis indicates that work climate exerts a more dominant influence compared to leadership style. These results underscore the importance of fostering a supportive and conducive work environment to enhance employee satisfaction. Although leadership style has a relatively smaller effect, it still plays a critical role in shaping employees' attitudes and performance. The study recommends that organizations focus on improving both the work climate and leadership practices to promote higher job satisfaction and overall organizational effectiveness. Future studies may explore additional variables such as employee motivation or organizational culture to provide a more comprehensive understanding of job satisfaction dynamics.